Aplikasi Kehadiran Mahasiswa Secara Otomatis Dengan Smartphone - Nur Ahmad; Saiful Bahri; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2020)
The study is titled Online Student Attendance Application with Smartphone. With affordable education costs and a very strategic location, Boyolali University is one of the universities in Boyolali district. Boyolali University is ready to meet the challenges of the education world towards competition at regional and national levels. The Boyolali University attendance process is still manual by using the attendance book, this makes students often commit attendance cheating with the help of other students who attend lectures and cause lecturers to find it difficult to develop the potential of students. The purpose of this research is to design, implement, and test student attendance applications automatically with a smartphone at Boyolali University, producing an online attendance application to improve the learning process and reduce student cheating while doing attendance at Boyolali University. The research methodology used is the Iconix process, object modeling using UML. For coding using php Mysql, and android client. The results achieved are an online attendance application to facilitate lecturers in making attendance and improving the learning process for students.